PRAKTIK EKOWISATA DI KAMPUNG TRADISIONAL BENA, DESA TIWORIWU KABUPATEN NGADA, PROVINSI NUSA TENGGARA TIMUR - Amtiran, Muni Imelda; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i02.p17, 2016)
The participation of local community is very needed in practicing ecotourism at Bena traditional village to support their ecotourism development. Ecotourism is an alternative tourism that has advanced and nature base by focus and experience on nature along with giving the lowest impact on the environment. Based on the statement above this research is important to be done in order that environment conservation and their culture be still maintained by the local community besides it becomes an example of model or example for the other village. It also becomes a source of income that can improve the local community economic of Bena traditional village. The method that used to colect the data in this study was observation method, interviewing method and documentation. The data was used qualitative and quantitative by data source, primary and secondary data. Purposive sampling technique was used to get the information from informant determaining and data analysis is used qualitative descriptive by ecotourism practice concept approach. The result of this study showed that the local community kept their nature conservation in practicing ecotourism in Bena village. The local community developed their ecotourism dominantly as one of activity tourism in Bena.
Keywords: Ecotourism, local community, development.